Excellence in public service - Hota, P.C. (2006)
In India, public servants displayed a high level of dedication and competence in performing their duties in the initial years of Indian Administrative Service. The respect they commanded was eroded progressively by successive political masters as also the sporadic instances of corruption and political nexus that swelled in numbers by each passing year. This article examines the core issue of how to restore the credibility of public service as an institution of sound governance and restore civil servants their self-respect. It examines viability of Civil Service Act as an institutional arrangement to ensure excellence in public service. This excellence can also be achieved through a concerted effort by public servants as a class. - Reproduced.
Keywords: Civil service - India; Civil service